Rule of wolves / Leigh Bardugo. - Bardugo, Leigh (King of scars duology., 2022)
As Fjerda's massive army prepares to invade, Nikolai Lantsov will summon every bit of his ingenuity and charm - and even the monster within - to win this fight. But a dark threat looms that cannot be defeated by a young king's gift for the impossible.